2022
DOI: 10.21203/rs.3.rs-2308084/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and genotype distribution of HPV infection among women in Xiamen, China

Abstract: Objective: Cervical cancer is extremely associated with human papillomavirus (HPV) infection and genotype distribution of HPV varies geographic regions. This study aimed to evaluate the prevalence of HPV and genotype distribution among female populations in Xiamen, Fujian Province, which can be conducive for local government to formulate cervical cancer screening and HPV vaccine strategies. Methods: Clinical specimens were collected from 47926 participants aged 16-92 years at Women and Children’s Hospital, Xia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It has been established that HPV genotype distribution varied greatly by geographic region, with HPV‐16 retaining the most common type globally but HPV52 and 58 being more prevalent in Eastern Asia 32,33 . Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population 9,29,34–38 . In this study, we used pooled data from nine population‐based cervical cancer screening studies from six parts of China and identified that the five most frequently detected genotypes were HPV52, 16, 58, 68, and 51.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that HPV genotype distribution varied greatly by geographic region, with HPV‐16 retaining the most common type globally but HPV52 and 58 being more prevalent in Eastern Asia 32,33 . Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population 9,29,34–38 . In this study, we used pooled data from nine population‐based cervical cancer screening studies from six parts of China and identified that the five most frequently detected genotypes were HPV52, 16, 58, 68, and 51.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population. 9,29,[34][35][36][37][38] In this study, we used pooled data from nine F I G U R E 2 HPV genotype distribution among all women (A) and stratified by pathology grade (B) for women with normal histology, (C) for women with CIN1, (D) for women with CIN2, and (E) for women with CIN3+. CIN1, cervical intraepithelial neoplasia grade 1; CIN2, cervical intraepithelial neoplasia grade 2; CIN3+, cervical intraepithelial neoplasia grade 3 or higher; HPV, human papillomavirus.…”
Section: Discussionmentioning
confidence: 99%